TOPIC CRITICAL ANALYSISTAX COMPLIANCE (TAX COMPLIANCE) IN A BIBLIOMETRIC PERSPECTIVE - Perdana, Riza; Tjaraka, Heru (Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to map, test, and analyze Tax Compliance articles that have been published in Scopus indexed international journals. This research also provides a mapping of the research sector that has never been done in the context of the theme of Tax Compliance. This study uses a qualitative method with a Bibliometric approach. Bibliometric research is a part of the Systematic Literature Review technique that examines bibliographic data in an article. This study analyzed 994 articles from 363 Scopus indexed international journals from 1960 - 2022. The results showed that (1) Kirchler was the most prolific writer with 45 articles, (2) the USA was the most productive country with 140 articles, (3) the University of Vienna as the most productive affiliate with 118 articles, and (4) the Journal of Economic Psychology as the most productive journal with 809 articles. This research contributes to the determination of research gaps and suggestions for subsequent research topics to researchers.